The Study of Radioactive Fallout Source of Low-Equivalent Nuclear Bursts Based on Nuclear Cloud Simulation Using the CFD-DPM - Yangchao Li; Qiang Liu; Wei Liu; Wenshuang Xian; Feifei Li; Kai Zhang (Atmosphere)
The activity-height distribution of radioactive particles in the stabilization cloud of a nuclear burst plays a crucial role in the radioactive fallout prediction model, serving as the source for transport, diffusion, and dose rate calculation modules. A gas-particle multiphase flow solver was developed using the OpenFOAM Computational Fluid Dynamics (CFD) library and discrete phase method (DPM) library under a two-way coupling regime to simulate the U.S. standard atmosphere of 1976 with good stability. The accuracy of the numerical model was verified through low-equivalent nuclear weapons tests, including RANGER-Able and BUSTER-JANGLE-Sugar, depicting reasonable spatio-temporal changes in cloud profiles. The initialization module of the Defense Land Fallout Interpretative Code (DELFIC) and activity-size distribution, which considered fractionation, were employed for nuclear fireball and radioactive particle initialization. Simulations indicated that the activity-height distribution of the stabilization cloud mainly concentrated on the lower third of air burst cloud caps, while settling near the burst center for surface or near-surface bursts. This study has confirmed the effectiveness of the gas-particle flow solver based on the CFD-DPM method in simulating low-equivalent nuclear clouds and enriching research on radioactive fallout prediction models.